Recruitment of Mobility Limited Older Adults Into a Facility-Led Exercise-Nutrition Study: The Effect of Social Involvement. (20th March 2015) - Corcoran, Michael P.; Nelson, Miriam E.; Sacheck, Jennifer M.; Reid, Kieran F.; Kirn, Dylan; Fielding, Roger A.; Folta, Sara C.
Abstract: Purpose of the Study: Older adults are among the most challenging population groups to enroll into health-related research. This article describes two methods used by investigators to recruit mobility limited older adults residing at assisted living or senior housing (SH) facilities into a facility-led exercise-nutrition research study. Design and Methods: Sedentary older adults were recruited from 42 different assisted living facilities (ALFs) or SH communities. Two different recruitment approaches were used: At 22 sites, investigators conducted heavily advertised informational sessions to recruit participants (Info only). At 20 locations, these sessions were preceded by attendance of a study team member at various activities offered by the facility over the preceding 2 weeks (activity attendance). Population reach, enrollment, personnel cost, and time required to recruit at least five participants at each facility was measured. Reasons for declining participation and withdrawal rate were also measured. Results: Sixty percent more residents elected to be screened for eligibility when study personnel attended an activity offered by the facility. Activity attendance resulted in significantly less time, costs, and participant withdrawals compared with facilities with no activity attendance. Implications: Study team member attendance at activities offered by senior living facilities reduces cost and duration of recruitment and improves study retention. Interventions targeting this demographic are likely to benefit from deliberately building trust and familiarity among the resident population at senior living communities as part of the recruitment process.